PENGARUH MODEL KOOPERATIF TIPE GROUP INVESTIGATION TERHADAP HASIL BELAJAR SISWA DITINJAU DARI KEMANDIRIAN BELAJAR - Syahrir, Nasrun (Almeera Education, 2024)
This research is a quantitative study with a quasy experiment research method involving two groups, namely the experimental group and the control group. The purpose of this study was to analyze the interaction effect of Group Investigation (GI) learning method and learning independence on mathematics learning outcomes. This research was conducted at SMPN 17 Makassar. The affordable population in this study were seventh grade students of SMPN 17 Makassar. While the research sample was randomly selected two classes from all VII classes of SMPN 17 Makassar with the assumption that all classes were homogeneous. The research method used is a quasy experimental with the research hypothesis test technique used is two-way ANOVA with factorial 2 x 2. The data analysis requirements test used is normality test and homogeneity test. The test results showed that all data groups were normally distributed and homogeneous. The results of hypothesis testing show that there is no interaction effect of Group Investigation (GI) learning method and learning independence on math learning outcomes. Based on the results of this study, it is sought that teachers in learning mathematics apply the Group Investigation (GI) learning method and try to increase student learning independence